2006
DOI: 10.1037/1064-1297.14.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic nicotine on responses maintained by primary and conditioned reinforcers in rats.

Abstract: There is growing recognition that nonnicotine factors, such as the sensory stimuli associated with smoking, can play a critical role in the maintenance of cigarette smoking. However, little is known about the effects of nicotine on responding maintained by these stimuli, which are assumed to be conditioned reinforcers. The authors used an animal model to examine the acute and chronic effects of nicotine on responses maintained by food and conditioned reinforcers (i.e., lights) and responses in the absence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 29 publications
7
46
0
Order By: Relevance
“…An alternative possibility is that the responses reflected the activity of the same circuit. Indeed, previous work has shown that acute or chronic nicotine exposure enhances responses to food cues in animal models (21,(69)(70)(71)(72). If this effect is true, an important concern to address in future research is how the ability of nicotine to enhance responses to food is associated with the anorectic effects of this substance.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is that the responses reflected the activity of the same circuit. Indeed, previous work has shown that acute or chronic nicotine exposure enhances responses to food cues in animal models (21,(69)(70)(71)(72). If this effect is true, an important concern to address in future research is how the ability of nicotine to enhance responses to food is associated with the anorectic effects of this substance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serving as a weak primary reinforcer, there is growing support for an additional role of nicotine as a reinforcer enhancer (Donny et al 2003;Chaudhri et al 2006b;Raiff and Dallery 2006;Palmatier et al 2007;Liu et al 2007). The reinforcer-enhancer role was suggested because nicotine, either delivered contingent or noncontingent on a response, increased responding maintained by primary reinforcing visual stimuli (Donny et al 2003;Palmatier et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the generality of the reinforcer-enhancing account of nicotine, Raiff and Dallery (2006) employed an observing response procedure, which has been used to examine conditioned reinforcement (e.g., Dinsmoor et al 1972;Lieving et al 2006;Shahan et al 2006). The first part of the procedure involves illuminating one stimulus (e.g., continuous houselight; S+) during periods of food availability and a different stimulus (e.g., blinking houselight; S−) during periods of extinction (i.e., no food availability).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations